Lightning Shielding Failure Analysis of High Voltage Transmission Lines Based on Leading Development Model. Issue 3 (July 2021) - Liu, Yonghuan
Abstract: Lightning strikes are one of the important causes of line faults. With the increase of voltage levels, the proportion of short-circuit trip accidents caused by shielding strikes is increasing. Therefore, accurate evaluation of the line's shielding lightning resistance is important for power systems. Its safe and stable operation is of great significance. In this paper, based on the derivation of the pilot development model (LPM) for evaluating the shielding characteristics of the line, taking the 500kV single-circuit line network of the East China Power Grid as the research object, the lightning shielding trip rate and related influencing factors are analyzed and calculated, and the methods for enhancing the lightning protection performance are given. Measures.